ASIMETRI INFORMASI, FAKTOR INDIVIDUAL DAN FRAUD PENGADAAN BARANG/JASA - Laeli Budiarti; Ananti Putri Rahayu; Sudjono Sudjono (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The purpose of this study is to determine the effect of information asymmetry and invidual factors such as compensation satisfaction, locus of control and competency on the tendency for doing fraud in procurement of goods/services. The population in this study are all employees of Procurement Services Unit (ULP), Procurement Official (PP) and Committing Officer (PPK) in all State Universities in DKI Jakarta Province. This research uses saturated sampling technique, where the entire research population is used as respondent. Multiple linear regression is used to analysis the data. The results shows that asymmetry of information has no significant influence on the tendency of individuals in fraud procurement of good/services. Compensation satisfaction has no significant influence on individual tendencies in fraud procurement of goods/services. Moreover, External locus of control and competence have a positive influence and significant on the tendency of individuals to commit fraud in procurement of goods/services